Gateway discovery and selection scheme for Mobile Ad Hoc NEMO - Mahmood, Zainab Senan (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
The fast growing of the Internet applications and the need of the continuous ongoing connection brought new challenges for researchers to provide new solutions to guarantee the Internet access for mobile hosts and networks. The globally reachable, Home-Agent based, and infrastructure Network Mobility (NEMO) and the local, multi-hop, and infrastructure-less Mobile Ad hoc Network (MANET) developed by Internet Engineering Task Force (IETF) are supporting different topologies of the mobile networks. A new architecture was proposed to deal with the inefficiency of the Nested NEMOs as well as the global connectivity issues of MANET by combining both topologies to obtain Mobile Ad Hoc NEMO (MANEMO). However, the integration of NEMO and MANET introduces many challenges such as the redundant tunnel problem and Exit Router selection when multiple Exit Routers to the Internet exist. This research aims to propose MANEMO Gateway Discovery and Selection Scheme (MGDSS) which discovers and selects the gateway which improves the performance and the robustness of the network regardless of routing protocol used. This is done by extending the Tree Discovery Protocol (TDP) used by NEMO BSP and the Neighborhood Discovery protocol used by MANET. Every Mobile Router (MR) receives the information about all the Internet gateways in the network and selects the gateway based on multiple criteria: the hop count, the nested level, the stable time and the number of nodes registered at the intermediate nodes. The routing of packets in the MANEMO is proposed to be based on the selected gateway, as for NEMO gateway the tree structure will be used and for MANET gateway it depends on the routing protocol used. The OPNET Modeler 14.5 is used to evaluate the proposed scheme as well as the mathematical approach to benchmark with the standard NEMO BSP and the Multihomed MANEMO (M-MANEMO) approach. The results show that the average data packets dropped in WLAN connecting the MRs of the proposed scheme is 28.6% less compared to the NEMO BSP and 63% compared to the M-MANEMO. With fast mobility, the average WLAN delay of M-MANEMO is 14.3% more than the other two approaches. Also in a larger scale MANEMO with high traffic load and fast mobility, the MGDSS outperforms the M-MANEMO with reduced end-to-end delay around 21.6%. Whereas NEMO BSP has 68.7% more end-to-end delay compared to MGDSS. These delays cause the MGDSS to have 66.6% less voice jitter compared to M-MANEMO.